what is a correct first step in solving the inequality –4(3 – 5x)≥ –6x 9? –12 – 20x ≤ –6x 9 –12 – 20x ≥ –6x 9 –12 20x ≤ –6x 9 –12 20x ≥ –6x 9

Respuesta :

[tex]-4(3-5x)\geq-6x\pm9\\\\-4(3)-4(-5x)\geq-6x\pm9\\\\\boxed{-12+20x\geq-6x\pm9}[/tex]

we have

[tex]-4(3-5x) \geq -6x+9[/tex]

Step 1

Applying the distributive property in the left side ( Multiply the factors on the left side)

[tex]-4(3-5x) \geq -6x+9\\- 4*3+4*5x\geq -6x+9\\-12+20x\geq -6x+9[/tex]

therefore

the answer is

[tex]-12+20x\geq -6x+9[/tex]